Dynamic labour demand with lumpy and kinked adjustment costs - Paola Rota (Fondazione Eni Enrico Mattei (FEEM), 2001)
We analyse the dynamics of firms' employment decisions which underlie lumpy and kinked adjustment costs. We consider a dynamic structural model in which, in each period, firms face a choice of whether to vary the labour input or to postpone the adjustment to the future. By exploiting the first order condition for optimality, we derive a semi-reduced form in which firms' intertemporal employment are defined by a standard static marginal productivity condition augmented by a forward-looking term. In this way we obtain a marginal productivity equilibrium relation which takes into account the future alternatives of adjustment or non-adjustment that firms face as the result of the presence of fixed and linear adjustment costs. Linear costs amount to 35% of average labour costs and fixed costs are estimated to be about 3.65 times average unit labour costs.
Keywords: J32; C23; 330; adjustment costs; dynamic labour demand; discrete decision process; Arbeitsnachfrage; Anpassungskosten; Entscheidung; Verarbeitendes Gewerbe; Schätzung; Italien